STRATEGI GURU PENDIDIKAN AGAMA ISLAM DALAM PEMBINAAN AKHLAK KELAS X BAHASA di SMAS AN-NUR BULULAWANG MALANG - Muhammad Darul Huda; Abdul Jalil; Muhammad Sulistiono (Vicratina : Jurnal Ilmiah Keagamaan, 2020)
Islamic religious education teachers play an important role in the process of fostering the morals of their students. For the success of the coaching process, Islamic religious education teachers must be able to use a variety of strategies in forming morals. Moral is an important thing that must be owned by everyone, especially students, because of the pros and cons of someone seen from the morals they have. In this modern era a lot of phenomena arise about the decline in morals owned by students, with these developments causing a negative impact on all groups, including students. This is where the role of educators, especially Islamic religious education teachers, is to foster student morals to avoid behavior that is not in accordance with Islamic teachings. In overcoming this, a strategy is needed to foster student morals.